1993
DOI: 10.1002/j.1460-2075.1993.tb05981.x
|View full text |Cite
|
Sign up to set email alerts
|

The cdc2-related protein p40MO15 is the catalytic subunit of a protein kinase that can activate p33cdk2 and p34cdc2.

Abstract: Activation of the cyclin‐dependent protein kinases p34cdc2 and p33cdk2 requires binding with a cyclin partner and phosphorylation on the first threonine residue in the sequence THEVVTLWYRAPE. We present evidence that this threonine residue, number 160 in p33cdk2, can be specifically phosphorylated by a cdc2‐related protein kinase from Xenopus oocytes called p40MO15. Binding to cyclin A and phosphorylation of this threonine are both required to activate fully the histone H1 kinase activity of p33cdk2. In cell e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
195
2

Year Published

1996
1996
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(205 citation statements)
references
References 59 publications
8
195
2
Order By: Relevance
“…The observed IFN-a-mediated early inhibition (6 ± 24 h treatment) of CDK-4-associated H-1 kinase activity was not due to the inhibitory e ect of CDK-4 expression, as IFN-atreatment did not inhibit the expression of CDK-4 protein upto 24 h treatment ( Figure 2c). Results in Figure 2d show that the induced p21 WAF1 also interacts with CDK-4, in addition to the reported interaction with CDK-2 (Poon et al, 1993;Matsuoka et al, 1994). Since the kinetics of restoration (due to depletion of p21 WAF1 ) of H-1 activity associated with CDK-2 or CDK-4 was in-parallel with the kinetics of p21 WAF1 induction, these results suggested that the observed inhibition of CDK-2 or CDK-4 kinase activity in IFNa-treated Daudi cells may be due to conditional induction of CDK-inhibitor p21 WAF1 by IFN-a.…”
Section: Ifn-a Inhibits Rb Protein Phosphorylation and Cdkassociated supporting
confidence: 60%
See 1 more Smart Citation
“…The observed IFN-a-mediated early inhibition (6 ± 24 h treatment) of CDK-4-associated H-1 kinase activity was not due to the inhibitory e ect of CDK-4 expression, as IFN-atreatment did not inhibit the expression of CDK-4 protein upto 24 h treatment ( Figure 2c). Results in Figure 2d show that the induced p21 WAF1 also interacts with CDK-4, in addition to the reported interaction with CDK-2 (Poon et al, 1993;Matsuoka et al, 1994). Since the kinetics of restoration (due to depletion of p21 WAF1 ) of H-1 activity associated with CDK-2 or CDK-4 was in-parallel with the kinetics of p21 WAF1 induction, these results suggested that the observed inhibition of CDK-2 or CDK-4 kinase activity in IFNa-treated Daudi cells may be due to conditional induction of CDK-inhibitor p21 WAF1 by IFN-a.…”
Section: Ifn-a Inhibits Rb Protein Phosphorylation and Cdkassociated supporting
confidence: 60%
“…One of the key phosphorylation event controlling CDKs activity is the activation of phosphorylation on a residue in various CDKs, corresponding to threonine (Thr) 161 in human prototypic CDK-1. Phosphorylation of this residue is positively required for function of both human and yeast CDK-1 and recent reports have shown that an analogous phosphorylation step is essential for activities of CDK-2 and CDK-4 (Poon et al, 1993;. A kinase responsible for phosphorylating the Thr 161 of CDK-1 and the corresponding residue in other CDKs (T 172 in CDK-4, T 160 in CDK-2) has been identi®ed in various organisms and designated CAK, for CDK-activating kinase (also known as CDK-7).…”
Section: Introductionmentioning
confidence: 99%
“…GST-Cdk2 (human) in pGEX-2T was as described (Poon et al, 1993), and cdk2 (Xenopus) in pET8c for reticulocyte lysate translation was a gift from T Hunt (ICRF, South Mimms). GST-tagged human p21 (GST-p21 in pGEX-KG) and histidine-tagged human p21 (p21-H6 in pET21d) were as described (Poon et al, 1996).…”
Section: Constructsmentioning
confidence: 99%
“…Thrombin digestion of GST-fusion proteins was as described (Poon et al, 1993). Transcription of mRNA in vitro and translation in the mRNA-dependent reticulocyte lysate in the presence of 35 Smethionine was as described (Jackson and Hunt, 1983).…”
Section: Expression and Puri®cation Of Recombinant Proteinsmentioning
confidence: 99%
“…A C-terminal fragment of the human retinoblastoma (Rb) protein (aa 773 ± 928) fused to glutathione-S-transferase (GST), encoded by the pGEX-GST-C-Rb plasmid (provided by E Harlow and W Kaelin) was isolated as described (Poon et al, 1993). Tet-myc cells were trypsinized, pelleted and quick frozen in liquid nitrogen at various times following serum starvation.…”
Section: Kinase Assaysmentioning
confidence: 99%